Environmental Kuznets Curve hypothesis from lens of economic complexity index for BRICS: Evidence from second generation panel analysis - Agozie, D.Q.; Agozie, D.Q.; Bekun, F.V.; Ozturk, I.; Taha, A. (Sustainable Energy Technologies and Assessments, 2022)
The present study contributes to the ongoing discussion on environmental sustainability, energy efficiency for the case of Brazil, Russia, India, China, and South Africa economies by investigating the dynamic connection regarding foreign direct investment, economic complexity index, renewable energy, natural resources, urbanization, and CO2 emission for annual frequency data from 1990 to 2019. The present study employs robust econometric techniques including Augmented Mean Group with Fully Modified-Ordinary Least Squares estimators as estimation techniques. Empirical outcome shows both inverted U-Shaped and N-Shaped EKC relationship between ECI and CO2 emission. The empirical findings also lend support to the Pollution Haven Hypothesis, which suggest that foreign direct investment influx is a contributing factor to environmental degradation in Brazil, Russia, India, China, and South Africa economies. Furthermore, renewable energy and the interaction between economic complexity index and urbanization is found to have adverse impact on emission while natural resources and urbanization have positive impact on the environment. Finally, the results from the Dumitrecu and Hurlin causality reveals a bi-directional causality between economic complexity and CO2 emission. Similar causality is found between economic complexity index and urbanization and CO2 emission while a one-way causality is seen running from foreign direct investment to CO2 emission over study period. These findings encourage authorities of the investigated countries to offer a broader energy strategy on alternative energies i.e., renewables improve Brazil, Russia, India, China, and South Africa environmental quality. Furthermore, emphasis on economic strategies that foster a healthier manufacturing activity to engender environmental sustainability without compromise for economic prosperity should be pursued among the examined economies.
Research Article
Keywords: Economic complexity; SDGs; Carbon-reduction; Alternative energy; Emerging economies